Experimental study on the mechanism of sex difference in the risk of torsade de pointes - 阮燕菲 刘念 周强 李泱 王琳 (Chinese medical journal, 2004)
Background Torsade de pointes (TdP) is a form of polymorphic ventricular tachycardia featuring prolonged QT intervals. Female gender is associated with an increased risk of TdP. However, the causes of the sex difference in risk are poorly understood. Recently, transmural dispersion of repolarization (TDR) has been implicated in the genesis of TdP. Consequently, we compared TdP incidence and TDR between male and female rabbit hearts in order to investigate the mechanism of sex difference in TdP risk in rabbits in vitro.Methods By means of monophasic action potential recording techniques, the monophasic action potential of the epicardium, midmyocardium, and endocardium were simultaneously recorded using specially designed plunge-needle electrodes placed across the left ventricular free wall of both female(n =8) and male (n =8) rabbit hearts puffused by the Langendorff method. TdP was induced by bradycardia, d-sotalol, and Iow-K^+, Mg^2+ Tyrode solution.Results TDR measurements in all three myocardial layers of male and female rabbit hearts were (18±2) ms and (21±2) ms, respectively (n =8, P >0. 05). After peffusion with d-sotalol, the 90% monophasic action potential duration was prolonged in both male and femlae rabbits. TDR in male andfemale rabbit hearts increased to (29±2) ms and (61±2) ms, respectively, a difference that is significant. Eight female rabbit hearts had early afterdepolarization and 7 of them developed TdP.Seven male rabbit hearts had early after depolarization, but only one of these hearts developed TdP.Conclusion Greater TDR may play an important role in the higher incidence of TdP in female rabbit hearts.